Industry switching in developing countries - Carol Newman; John Rand; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Firm turnover (i.e. firm entry and exit) is a well-recognized source of sectorlevel productivity growth across developing and developed countries. In contrast, the role and importance of firms switching activities from one sector to another is little understood. Firm switchers are likely to be unique both from newly established entrants and exiting firms that close down. We build an empirical model that examines switching behaviour based on data from Vietnamese manufacturing firms during the period 2001-08. Our diagnostic shows that switching firms have different characteristics and behaviour as compared to entry and exit firms. They tend, inter alia, to be labour-intensive and seek out competitive opportunities in labour-intensive sectors in response to changes in the market environment. We also show that resource reallocations resulting from switching form an important component of productivity growth.
Keywords: D21; L6; O14; 330; firm dynamics; sector switching; efficiency; Vietnam; Markteintritt; Marktaustritt; Verarbeitendes Gewerbe; Unternehmensentwicklung; Vietnam